Persistent Wnt/β‐Catenin Signaling Determines Dorsalization of the Postnatal Subventricular Zone and Neural Stem Cell Specification into Oligodendrocytes and Glutamatergic Neurons. (17th April 2014) - Azim, Kasum; Fischer, Bruno; Hurtado‐Chong, Anahi; Draganova, Kalina; Cantù, Claudio; Zemke, Martina; Sommer, Lukas; Butt, Arthur; Raineteau, Olivier
Abstract: In the postnatal and adult central nervous system (CNS), the subventricular zone (SVZ) of the forebrain is the main source of neural stem cells (NSCs) that generate olfactory neurons and oligodendrocytes (OLs), the myelinating cells of the CNS. Here, we provide evidence of a primary role for canonical Wnt/ β ‐catenin signaling in regulating NSC fate along neuronal and oligodendroglial lineages in the postnatal SVZ. Our findings demonstrate that glutamatergic neuronal precursors (NPs) and oligodendrocyte precursors (OPs) are derived strictly from the dorsal SVZ (dSVZ) microdomain under the control of Wnt/ β ‐catenin, whereas GABAergic NPs are derived mainly from the lateral SVZ (lSVZ) microdomain independent of Wnt/ β ‐catenin. Transcript analysis of microdissected SVZ microdomains revealed that canonical Wnt/ β ‐catenin signaling was more pronounced in the dSVZ microdomain. This was confirmed using the β ‐catenin‐activated Wnt‐reporter mouse and by pharmacological stimulation of Wnt/ β ‐catenin by infusion of the specific glycogen synthase kinase 3 β inhibitor, AR‐A014418, which profoundly increased the generation of cycling cells. In vivo genetic/pharmacological stimulation or inhibition of Wnt/ β ‐catenin, respectively, increased and decreased the differentiation of dSVZ‐NSCs into glutamatergic NPs, and had a converse effect on GABAergic NPs. Activation of Wnt/ β ‐catenin dramatically stimulated the generation of OPs, but its inhibition had no effect, indicating other factors act in concert with Wnt/ β ‐catenin to fine tune oligodendrogliogenesis in the postnatal dSVZ. These results demonstrate a role for Wnt/ β ‐catenin signaling within the dorsal microdomain of the postnatal SVZ, in regulating the genesis of glutamatergic neurons and OLs. Stem Cells 2014;32:1301–1312